Correlation between total extractable proteins and allergen levels of natural rubber latex gloves - Yip Esah; Alenius H; Palosuo T; Turjanmaa K (Journal of Natural Rubber Research, 1997)
Certain proteins or peptides eluting from natural rubber (NR) latex products can cause immediate hypersensitivity reactions (Type I allergy) in subjects sensitised to them. The amount of total extractable proteins in manufactured latex products is believed to reflect reasonably well their corresponding allergenic protein level, but only a few studies have been published to substantiate this. The aim of the present study is to compare a widely used total protein measurement assay, namely, the RRIM modified Lowry test(EP RRIM), to latex allergen analysis, carried out by specific IgE-ELISA-inhibition tests. A series of 46 widely marketed medical NR latex gloves was investigated. Their EP RRIM values ranged from <20 mg/g to 1290 mg/g, and their allergen content varied from <1AU/ml to 570 AU/ml. In the measurement of allergen contents, the reference allergen mixture was prepared from serum proteins of fresh Hevea latex, and IgE antibodies were sourced from both adults and spina bifida children sensitive to latex. Results showed that the allergen levels were very well correlated with the total extractable protein contents (coefficient r = 0.89, P<0.001, n = 46). With the exception of a few, gloves with high total extractable proteins were generally found to have high allergen contents, and vice versa. Gloves with EP RRIM levels of 0.1mg/g or 100 mg/g and below always had very low allergen contents (<9AU/ml). These findings are consistent with those shown by the in-vivo skin-prick test reported earlier. More importantly, they confirm the very low allergen levels observed at EP RRIM levels of about mg/g and lower. Such information provides useful guideline for the manufacturing of reduced risk NR latex gloves.
Keywords: Latex gloves; Protein allergy